KORAK DO ZLATA - DRUGA STRANA KOMUNIKACIJSKE MEDALJE. Neverbalna komunikacija u sportu, II. dio - Bartoluci, Sunčica; Tomić, Diana (2014)
This, second, paper on non-verbal communication discusses the third aspect of the topic – body position and movements in the context of sports. Possible meanings of gestures, posture, touch, facial expressions, gaze and vocal expressions for communication are explained on the examples from athletic fields. The emphasis is put on the multidimensional information transferred non-verbally, the importance of their contextual interpretation and the risk of misinterpretation if a certain dimension is ignored. The paper also discusses the issue of universality of non-verbal cues ; cultural differences, individual differences in the awareness of nonverbal messages and the advantages that good readers of non-verbal cues have both as speakers and listeners.
HRV